1997
DOI: 10.5144/0256-4947.1997.20
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Neurological Problems in Diabetes Mellitus: Retrospective Analysis of Data from 1294 Patients

Abstract: Data from 1294 patients with diabetes mellitus admitted to the Endocrinology Department of the Institute of Medical Sciences, Srinagar, Kashmir, from 1986 to 1994, were analyzed for frequency of various neurological problems. Of 1294 patients, 46.29% had clinical evidence of one or more neurological problems. The frequency of neurological problems was significantly more in patients with type II diabetes mellitus (P<0.001). Predominant neurological problems included peripheral neuropathy (96.66%), stroke (5.51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(58 reference statements)
0
1
1
Order By: Relevance
“…This is an important observation which accords with the recent report by Al Rajeh et al 4 Adeuja and Osuntokun 12 in Nigeria had observed that diabetes and hypertension together were present in 10% of non-embolic ischemic brain infarctions, and in 8% of those with intracerebral hemorrhage. Zargar et al 17 found concomitant hypertension in 66.6% of diabetic patients with stroke, compared to our finding of 78%. About 62% of our hypertensive stroke patients had concomitant diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 55%
“…This is an important observation which accords with the recent report by Al Rajeh et al 4 Adeuja and Osuntokun 12 in Nigeria had observed that diabetes and hypertension together were present in 10% of non-embolic ischemic brain infarctions, and in 8% of those with intracerebral hemorrhage. Zargar et al 17 found concomitant hypertension in 66.6% of diabetic patients with stroke, compared to our finding of 78%. About 62% of our hypertensive stroke patients had concomitant diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 55%
“…This may be due to the low incidence of CAD in sub-Saharan Africans even among diabetics. In this regard, a review of ECG of diabetic Asian migrants in the UK showed ST-T wave abnormalities to be the most common finding [29] and ST-T wave abnormalities on ECG at rest have been shown to strongly correlate with silent ischemia. [30] LVH is the most frequent ECG abnormality, present in about 34% of diabetics which is similar to the reports of other studies.…”
Section: Discussionmentioning
confidence: 99%